2019
DOI: 10.1002/ajh.25660
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin‐release assay‐negative heparin‐induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is a prothrombotic drug reaction caused by platelet-activating anti-platelet factor 4 (PF4)/heparin antibodies. Pathogenic HIT antibodies can be detected by the serotonin-release assay (SRA), a platelet activation test. We have regarded the SRA performed in our medical community ("McMaster" SRA) as having high sensitivity and specificity. Recently, the concept of "SRAnegative HIT" has been proposed for enzyme-immunoassay (EIA)-positive/SRAnegative patients with a HIT-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 38 publications
4
67
1
Order By: Relevance
“…However, more recent studies 21 58 from our group do support the concept of SRA-negative HIT. In one study, we systematically evaluated 27 EIA-positive/SRA-negative samples by PF4-SRA; we found one patient with plausible SRA-negative HIT on both clinical and laboratory grounds.…”
Section: Sra-negative Hitmentioning
confidence: 54%
See 1 more Smart Citation
“…However, more recent studies 21 58 from our group do support the concept of SRA-negative HIT. In one study, we systematically evaluated 27 EIA-positive/SRA-negative samples by PF4-SRA; we found one patient with plausible SRA-negative HIT on both clinical and laboratory grounds.…”
Section: Sra-negative Hitmentioning
confidence: 54%
“…Our laboratory has independently shown that the sensitivity of our SRA could also be enhanced by measuring patient serum-dependent serotonin release in the presence of high concentrations of PF4 (50–100 μg/mL), rather than heparin, in a modified assay we called the “PF4-SRA.” 21 57 58 In our first report describing the PF4-SRA, 57 we found that the additional patients identified as having platelet-activating antibodies did not appear to have a clinical picture suggestive of HIT. In other words, it seemed plausible that (conventional) SRA-negative blood samples that tested positive in the PF4-SRA might be similar to SRA-negative/EIA-positive blood samples, in that the patients most likely did not have HIT.…”
Section: Sra-negative Hitmentioning
confidence: 86%
“…We agree that false‐positive enzyme immunoassay (EIA) detection of anti–platelet factor 4 (PF4)/heparin antibodies could explain the results we observed in patients 2 and 3, 2 and this has been the conventional interpretation when functional testing (such as the serotonin‐release assay [SRA]) returns negative. We suggested that a false‐negative SRA result could have explained our findings, as opposed to the contention by May et al that we concluded they were falsely positive, to broaden our discussion about SRA‐negative HIT, a relatively new and evolving clinical condition 3‐6 …”
contrasting
confidence: 53%
“…Given the importance of HIT ascertainment in this novel patient population, we recommend referral of EIA-positive or LIA-positive blood samples for testing by functional (platelet activation) assay, such as the SRA. However, given emerging data regarding occasional false-negative SRA results [ 114 ], we also suggest that SRA-negative blood samples (but with strong clinical suspicion of HIT corroborated by strong-positive EIA or LIA) be referred to a laboratory with experience in performing newer PF4-dependent platelet activation assays, such as the PF4-SRA [ 114 ], PF4/heparin-SRA [ 115 ], or the P-selectin expression assay [ 116 ].…”
Section: Hit As a Potential Complication Of Covid-19mentioning
confidence: 99%